La vitalité, la vie et le travail - Éric Hamraoui (Perspectives Interdisciplinaires sur le Travail et la Santé)
Vitality commonly refers not only to the very energy that characterizes life but also to one’s health, the basis of one’s bodily and mental vigour. However, this reciprocity in the determination of vitality and life seems to be both supported and contradicted in the new ways of organizing work and in government hygiene-inspired recommendations for health matters. The roles played by the ideology of risks and individual performance evaluations are, in my opinion, no less decisive in the genesis of this peculiar antagonism between vitality and life. We have chosen an approach that combines aspects of philosophical thought, the psychology of work, and public hygiene history, but that also includes elements of theology, sociology, and, to a lesser extent, of literature, in order to highlight the necessity to develop instruments that can determine the mechanisms leading to the exhaustion of life at work and resulting in numerous health problems and even suicide.